The differences in motor and cognitive abilities between the more and less successful 12-14 years old judokas - Drid, P.; Bala, G.; Obadov, S. (Archives of Budo, 2010)
This study attempted to single out factors related to success in judo in judokas aged 12-14 years. The authors of this work thought it was necessary to define both basic motor and cognitive profiles of judokas for the purpose of better recruitment for the sport as well as evaluation of the training process itself. Material and methods. Participants were assigned to either "Medallist" or "Non-medallist", according to their previous results in competitions at the national level. Medallist consisted of 83 children (54 boys, 13.07±0.21 yrs; and 29 girls, 13.08±1.48 yrs) who have, in the last two years, won one or more individual medals at the national championships. Non-medallist had 82 children (55 boys, 12.89±1.42 yrs; and 27 girls, 12.78±1.23 yrs) who still have not won a medal at the national championships. The battery of eight motor tests and The Raven's Standard Progressive Matrices used in this research. Results. The results of cognitive and motor abilities show that Medallist generally performed better in all tests than Non-medallist both for male and female judokas. The largest contribution to the differences specifically came from the Obstacle course backwards, Crossed-arm sit-ups, Standing broad jump and Bent-arm hang tests, as well as from cognitive abilities (assessed by the Raven's Standard Progressive Matrices). Conclusions. It can be concluded that the more successful judokas generally possess better cognitive abilities, coordination and strength than less successful ones.